The Views of Thai Buddhist Monks on a Good Death - Bumpenchit Sangchart; Suksan Promdee Ngamgam; Rawat Ekwuttiwongsa; Monthida Sangruangake (Universitas Ahmad Dahlan, 2020)
Background:When Buddhist monks were sick, they had to take care of themselves, or they will be taken care of by other monks. The care may be provided until they recover from the illness or throughout life. The monks who are the caregivers go through near-death and death experiences. The purpose of this phenomenological study was to investigate the meanings of a good death based on the experience of 13 Thai Buddhist monks that providing care for the sick monks until the sick monks passed away. Method:Purposeful sampling was used to select participants who voluntarily participated in the study. In-depth interviews were the main methods of data gathering. Established trustworthiness of a qualitative inquiry based on quality criteria of Lincoln and Guba. The methodological interpretations of Diekelmann and Allen established the thematic analysis of this study. Results:Six main themes and six subthemes of a good death emerged from participants which formed the basis of the findings reported: (a) free from suffering, consisting of 1) death without life's restraints, 2) peaceful death, and 3) death as a sleeping person (but not awake); (b) natural death with good deeds; (c) awareness of death, composed of (1) accepting death, (2) preparation before death, and (3) letting things go; (d) last spirituality becoming a mental charity; (e) resting in peace; and (f) nirvana. Â Conclusion: The results of the present study could fulfill and extend the meanings of good death to a wider and deeper which are different from the previous studies.